Diagnostic utility of imprint cytology of endoscopic gastric biopsy: A cyto-histo correlation study - Choudhary, Prabesh Kumar; Nepal, Niraj; Shrestha, Rishab; Adhikari, Utsav (Journal of Pathology of Nepal, 2019)
Background: Upper gastrointestinal endoscopy is a common procedure done for suspected cases of gastric malignancies. Histopathological examination of gastric tissue has been a gold standard for the diagnosis. Imprint smears of the gastric biopsy specimen is a useful and rapid alternative diagnostic tool. This study was conducted to assess the accuracy of gastric biopsy imprint cytology as compared to the histopathology. Materials and Methods: Imprint smears were made from all cases of gastric biopsy specimens taken from suspected cases of gastric malignancies. They were evaluated by three pathologists and categorized in to negative for malignancy, suspicious of malignancy and positive for malignancy. The diagnosis given by imprint smears was compared with histopathology. With the help of sensitivity, specificity & accuracy and Kappa score, the agreement between the imprint smear and histopathology was determined. Results: Among the total 79 cases, 49 cases were chronic non specific gastritis and 22 were adenocarcinoma. The sensitivity, specificity, and overall accuracy of gastric biopsy imprint smear were 92.0%, 98.11% and 94.93% respectively. Kappa core was 0.88. Conclusions: The gastric biopsy imprint smears is a rapid diagnostic tool and can be used routinely as an adjunct to histopathology in the diagnosis of gastric malignancies.